2016
DOI: 10.3389/fphys.2016.00499
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Molecular Genetics of Familial Hypertrophic Cardiomyopathy in South Asian Descendants

Abstract: The South Asian population, numbered at 1.8 billion, is estimated to comprise around 20% of the global population and 1% of the American population, and has one of the highest rates of cardiovascular disease. While South Asians show increased classical risk factors for developing heart failure, the role of population-specific genetic risk factors has not yet been examined for this group. Hypertrophic cardiomyopathy (HCM) is one of the major cardiac genetic disorders among South Asians, leading to contractile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 140 publications
0
19
0
Order By: Relevance
“…We found a high proportion of genotype-low prevalence in South Asian and Japanese people. 28,30 Because mutations in TPM1 are considered a very rare cause of HCM, its prevalence of 7.7% is an unusually high detection rate. 31 However, an HCM-causing mutation in TPM1, c.523G>A (p.Asp175Asn), was previously identified in a Finnish population with a similar prevalence (6.5%) as a founder mutation showing regional clustering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a high proportion of genotype-low prevalence in South Asian and Japanese people. 28,30 Because mutations in TPM1 are considered a very rare cause of HCM, its prevalence of 7.7% is an unusually high detection rate. 31 However, an HCM-causing mutation in TPM1, c.523G>A (p.Asp175Asn), was previously identified in a Finnish population with a similar prevalence (6.5%) as a founder mutation showing regional clustering.…”
Section: Discussionmentioning
confidence: 99%
“…TNNT2 (9.1%) and TNNI3 (4.5%) were identified as the next 2 most common causes of HCM after MYBPC3 and MYH7, in agreement with previous studies in several European and Asian populations. 23,26,28,30,33 Few mutations were found in non-sarcomeric genes. Except for P mutations identified in TCAP, the other variants were mostly classified as VUS, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In another study performed by Ronkaratti et al, in the Italian population, it is found that the frequency of mutations determined in the MYH7 gene was found to be very low. Many factors, such as modifying genes, epigenetic factors, microRNAs, posttranslational protein modifications, and environmental factors, may affect the clinical course of HCM disease [1,10]. Genetic studies are required to understand the clinical and prognostic heterogeneity of HCM.…”
Section: βMyhc Versus Mybp-c Gene Polymorphismsmentioning
confidence: 99%
“…Since the identiication of the irst locus for familial HCM and the irst mutation in MYH7-encoded beta-myosin heavy chain 20 years ago [25], over 1500 causal mutations associated with HCM encode sarcomeric proteins have been revealed [26]. According to gene susceptibility, HCM can be divided to "myoilament (sarcomeric) HCM," "Z-disk HCM," and "calcium-handling HCM," with "myoilament (sarcomeric) HCM" being the most common genetic form of HCM, account for 50% of all HCM cases [13]. Recently, large genotype-phenotype analysis correlation studies established implications for septal morphology, disease onset, and prognosis of certain sarcomeric genes, which may further facilitate commercialized genetic testing.…”
Section: Hypertrophic Cardiomyopathy-associated Genesmentioning
confidence: 99%
“…These mutations alter myocardial metabolism, resulting in increased wall thickness, cardiac storage abnormalities, and conduction irregularities second to multiple systematic disorders. The information of HCM susceptibility genes and HCM phenocopies are listed in Tables 2 and 3 [13,27,28].…”
Section: Hypertrophic Cardiomyopathy-associated Genesmentioning
confidence: 99%